2006
DOI: 10.1128/aem.02288-05
|View full text |Cite
|
Sign up to set email alerts
|

One Group of Genetically Similar Listeria monocytogenes Strains Frequently Dominates and Persists in Several Fish Slaughter- and Smokehouses

Abstract: Contamination of foods with the human pathogen Listeria monocytogenes may occur during processing, and the purpose of this study was to determine whether genetically similar strains colonize different processing plants or whether specific persistent strains are unique to each processing plant. We hypothesized that specific L. monocytogenes strains may be better adapted to specific environmental niches in the processing environment. L. monocytogenes contamination patterns were identified by the collection of 68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
87
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 25 publications
4
87
1
4
Order By: Relevance
“…Persistence may indicate deficiencies in sanitation procedures or potential niches in the processing environment where L. monocytogenes is protected from sanitation. While persistence of L. monocytogenes in meat processing plants (15,37,38,61) and in other plants (44,47,73) has previously been reported, identification of different PFGE types (as well as different molecular serotypes and lineages) associated with persistence in different plants (except for one PFGE type associated with persistence in two plants) clearly suggests that many different L. monocytogenes strains have the ability to establish persistent populations in processing plants.…”
Section: Discussionmentioning
confidence: 98%
“…Persistence may indicate deficiencies in sanitation procedures or potential niches in the processing environment where L. monocytogenes is protected from sanitation. While persistence of L. monocytogenes in meat processing plants (15,37,38,61) and in other plants (44,47,73) has previously been reported, identification of different PFGE types (as well as different molecular serotypes and lineages) associated with persistence in different plants (except for one PFGE type associated with persistence in two plants) clearly suggests that many different L. monocytogenes strains have the ability to establish persistent populations in processing plants.…”
Section: Discussionmentioning
confidence: 98%
“…Although it can be present in raw food materials, the processing plant environment is typically the immediate source of L. monocytogenes contamination of food products (5-8). Even though food processing equipment and facilities are cleaned frequently, some molecular subtypes of L. monocytogenes may persist in the food processing environment for many years (7-9).We have found that one specific molecular subtype of L. monocytogenes strains was dominant and persistent in several fish processing plants (8,10,11). Other subtypes were also isolated several times in the processing plants although not as frequently (8).…”
mentioning
confidence: 79%
“…La listeriosis no invasiva se manifiesta por síntomas de gastroenteritis (1,5,28,43), como diarrea, fiebre, cefalea y mialgias, y su periodo de incubación es corto (1,4,13,15,19,21,28,(43)(44)(45) Los alimentos considerados de alto riesgo para contraer listeriosis son los listos para el consumo (1,5,(9)(10)(11)16,17,28,(30)(31)(32)34,47,50,(63)(64)(65)(66). Ésta es una categoría amplia y heterogénea de alimentos (incluye bebidas) que no van a tener ningún proceso de cocción antes de su consumo, o que aparentemente son aptos para el consumo sin cocción (5,16), y varían de unos países a otros en relación con los hábitos alimentarios, la disponibilidad de la cadena de frío y la temperatura máxima en el punto de venta (1,5).…”
Section: Los Centers For Disease Control and Preventionunclassified